Evaluation of a rapid and automated heparin‐induced thrombocytopenia immunoassay. (15th April 2019) - Refaai, Majed A.; Conley, Grace; Ortel, Thomas L.; Francis, John L.
Abstract: Introduction: Heparin‐induced thrombocytopenia (HIT) is a potentially life‐threatening adverse reaction of heparin. Laboratory evaluation of HIT is often not available within a reasonable time. We evaluated the HemosIL ® HIT‐Ab(PF4‐H) (Instrumentation Laboratory), a rapid, on‐demand, fully automated, latex immunoturbidimetric assay (LIA). Materials and methods: Following determination of the LIA's reference interval and cutoff values, a multicenter study was conducted between March 2013 and June 2015. Plasma samples of HIT‐suspected patients (n = 632) were collected and evaluated by LIA on the ACL TOP ® Family systems (Instrumentation Laboratory), enzyme‐linked immunosorbent assays (EIA), and serotonin release assay (SRA). Patient characteristics, medical conditions, comorbidities, laboratory results, and medications were collected via medical chart review. The pretest clinical probability of HIT was also calculated for each patient. Results: Based on the 95% reference interval for healthy donors and HIT‐negative patients, a LIA value ≥1.0 U/mL was interpreted positive. The overall agreement of LIA versus EIA and SRA results were 90% (95% CI 88%‐92%) and 79% (95% CI 75%‐82%), respectively. The negative predictive value for LIA and EIA was comparable (87%) with SRA. The positive and negative percent agreements with the clinical probability were 89% (95% CI 69%‐97%) and 86% (95% CI 83%‐89%), respectively, with a negative predictive value of 99.6% (95% CI 98%‐100%). Discussion: Overall, the LIA results were comparable to those of EIA and SRA. This fully automated assay with a remarkable short analytical turnaround time of <20 minutes can be performed on‐demand, which would greatly facilitate more prompt management of HIT.